A Case of Severe Methotrexate Toxicity: Clinical Insights and Management - Pradnya Diggikar; Bhavya Sri Yammanaru; Tushar Pancholi; Manosri Mandadi; R Janani (Journal of Clinical and Diagnostic Research)
Methotrexate (MTX), first synthesised in 1947, originated as a derivative of aminopterin, a medication initially used to treat acute leukaemia in children. It shares similar properties with aminopterin and has since demonstrated remarkable efficacy in managing a wide array of complex dermatological and rheumatological conditions. Despite its therapeutic benefits, MTX toxicity, though rare, can lead to severe and potentially fatal consequences. This case report describes a 62-year-old male who developed erythematous lesions over his scalp, face, upper limbs, and torso following an excessive intake of MTX (120 mg/week for one month). The patient exhibited symptoms consistent with severe MTX toxicity, including mucositis, pancytopenia, and neutropenic sepsis. Despite timely initiation of leucovorin rescue therapy, intravenous hydration, urine alkalinisation, and aggressive management of neutropenic sepsis the patient’s condition deteriorated. Respiratory support was provided, but he ultimately succumbed to multi-organ dysfunction, underscoring the challenges associated with managing High-Dose MTX (HDMTX) toxicity. This report highlights the mechanisms of MTX toxicity, including its impact on folate metabolism and cell division, resulting in widespread tissue damage and immunosuppression. It emphasises the critical need for early recognition of toxicity symptoms, such as mucositis and bone marrow suppression, to promptly initiate life-saving interventions. Furthermore, it underscores the importance of patient education on MTX dosing and monitoring to prevent such adverse outcomes, illustrating the necessity for vigilant clinical management in patients receiving MTX therapy.